2023
DOI: 10.47836/mjmhs.19.s9.29
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Box Breathing on Sleep Disorders in Elderly at Tresna Werdha Social Institution

Amzal Mortin Andas,
Tukimin Sansuwito,
Faridah Mohd Said
et al.

Abstract: Introduction: The elderly population has become a global phenomenon. Almost every country in the world is experiencing an increase in the elderly population There are 703 million people in the world who are 65 or older. An elderly person will require more time to fall asleep and will experience less or shorter deep sleep. Factors that affect sleep disorders include age, history of illness, drinking coffee, and smoking cigarettes. To improve sleep quality in the elderly, a deep breathing relaxation technique, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…This outcome implies the absence of a discernible impact of pre-and post-sleep Sleep Hygiene control on sleep disturbances among the elderly residing in nursing homes. This finding is consistent with previous research, which similarly demonstrated no association between sleep hygiene and sleep disturbances using the Paired T-test, reporting statistical data with a p-value of 0.201 (pvalue > 0.005), signifying no significant difference before and after the control group intervention, indicating a lack of alteration in sleep disturbance levels (Andas et al, 2023).…”
Section: Effect Of Sleep Hygiene On Sleep Disorders In the Elderly Co...supporting
confidence: 92%
“…This outcome implies the absence of a discernible impact of pre-and post-sleep Sleep Hygiene control on sleep disturbances among the elderly residing in nursing homes. This finding is consistent with previous research, which similarly demonstrated no association between sleep hygiene and sleep disturbances using the Paired T-test, reporting statistical data with a p-value of 0.201 (pvalue > 0.005), signifying no significant difference before and after the control group intervention, indicating a lack of alteration in sleep disturbance levels (Andas et al, 2023).…”
Section: Effect Of Sleep Hygiene On Sleep Disorders In the Elderly Co...supporting
confidence: 92%